The Political Construction of Caste in South India - Vijayendra Rao Radu Ban (2007)
Are social institutions endogenous? Can measures of social diversity (e.g. fractionalization) be treated as exogenous variables in assessing their impact on economic and political outcomes? The caste system, which categorizes Hindus into endogamous and stratified social groups, is considered to be the organizing institution of Indian society. It is widely thought to have stayed stable for hundreds if not thousands of years -- so deeply resistant to change that it has been blamed for everything from (formerly) anemic Hindu rates of growth, to persistent inequality traps This paper uses a natural experiment -- the 1956 reorganization of Indian states alonglinguistic lines - to demonstrate that the number and nomenclature of castes has significantly changed in linguistically matched villages (i.e. "mistakes" in the reorganization) at the borders of these states. This shows that the caste system is not stable but a pliable institution - endogenous to political change.